ASSET-BACKED SECURITIES AS AN ALTERNATIVE TO MUSLIM INVESTMENTS IN THE MAQASHID ASY-SHARIAH FRAMEWORK - Muhammad Nashih; Much. Maftuhul Fahmi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
The advantages of asset-backed securities are many, namely that investors can invest in quality assets, there is low default due to the division of receivables into many debtors, it is suitable for investors with faster principal return needs, and the high-profit rating of asset-backed securities can increase the overall investment portfolio. This research examines the analysis of asset-backed securities (ABS) in the study of Maqashid Shariah. The method used in writing this research is library research, with data collection directed directly to the search for data and information through books, literature, or library materials, including written documents, photographs, pictures, and electronic documents. The results of this research indicate that ABS is a financial instrument in the form of a collective investment contract unit that contains a portfolio of financial assets. The practice of asset securitization in ABS transactions has several advantages and risks. ABS has participated in various state projects and is generally very useful. To unravel liquidity problems on the originator's side and at the same time present alternative instruments with low risk for investors, it can be seen that it has included Maqashid Ash-Shari'ah, namely Hifdz Al-Maal which is included in the Dharuriyyat category from the originator's side as a solution to asset liquidity and Hajiyyat from the investor's side.